Global biopesticide research trends: a bibliometric assessment - SINHA, BIKRAMJIT (The Indian Journal of Agricultural Sciences, 2012)
Combined realization of the negative effects of chemical pesticides and the positive attributes of biopesticide led to intensive research programmes on the later by both public and private institutions across nations. This has generated a knowledge pool and accumulated vast scientific literature. This paper tries to capture the nature of basic research in biopesticide and growth of the discipline during the last four decades. Bibliometric methods such as analysis of title-word and author keywords have been used to capture direction of research and to identify thrust areas of research. Growth of biopesticide research output has been encouraging, particularly since 1996. Microbial pesticides, particularly Bacillus thuringiensis-related research has dominated the discipline so far. The paper also identifies the leading institutes, countries, and the nature of inter-country as well as inter-institutional collaboration. As in most other disciplines of science, United States had an upper hand in biopesticide research, followed distantly by India. Two aspects that need immediate attention are the decline in participation of industry and international collaboration in biopesticide research, both of which are critical for developing cost-effective and environment-friendly pesticides having world-wide application.